Enhanced power quality based single phase photovoltaic distributed generation system. Issue 8 (2nd August 2016) - Panda, Aurobinda; Pathak, M. K.; Srivastava, S. P.
ABSTRACT: This article presents a novel control strategy for a 1-ϕ 2-level grid-tie photovoltaic (PV) inverter to enhance the power quality (PQ) of a PV distributed generation (PVDG) system. The objective is to obtain the maximum benefits from the grid-tie PV inverter by introducing current harmonics as well as reactive power compensation schemes in its control strategy, thereby controlling the PV inverter to achieve multiple functions in the PVDG system such as: (1) active power flow control between the PV inverter and the grid, (2) reactive power compensation, and (3) grid current harmonics compensation. A PQ enhancement controller (PQEC) has been designed to achieve the aforementioned objectives. The issue of underutilisation of the PV inverter in nighttime has also been addressed in this article and for the optimal use of the system; the PV inverter is used as a shunt active power filter in nighttime. A prototype model of the proposed system is developed in the laboratory, to validate the effectiveness of the control scheme, and is tested with the help of the dSPACE DS1104 platform.